2020
DOI: 10.3390/ijerph17197196
|View full text |Cite
|
Sign up to set email alerts
|

Health Behaviors and Health Status among Middle-Aged and Older Adults with Chronic Diseases in Taiwan

Abstract: Changes in lifestyle behaviors may effectively maintain or improve the health status of individuals with chronic diseases. However, such health behaviors adopted by individuals are unlikely to demonstrate similar patterns. This study analyzed the relationship between the heterogeneous latent classes of health behavior and health statuses among middle-aged and older adults with hypertension, diabetes, or hyperlipidemia in Taiwan. After selecting 2103 individuals from the 2005 and 2009 Taiwan National Health Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 42 publications
1
10
0
1
Order By: Relevance
“…Furthermore, many countries have demonstrated that certain health behavior patterns exert synergistic effects on mortality, morbidity, subjective well-being, and happiness. As such, many of these countries have exerted effort to adopt integrated strategies for promoting health behavior patterns [ 25 , 34 36 , 54 , 55 , 92 ]. Nevertheless, researchers have yet to reach a consensus on the direction of the relationship between happiness and health behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, many countries have demonstrated that certain health behavior patterns exert synergistic effects on mortality, morbidity, subjective well-being, and happiness. As such, many of these countries have exerted effort to adopt integrated strategies for promoting health behavior patterns [ 25 , 34 36 , 54 , 55 , 92 ]. Nevertheless, researchers have yet to reach a consensus on the direction of the relationship between happiness and health behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple health behaviors exert synergistic effects. Therefore, research on the clustering of multiple health behaviors and their relationship with health outcomes is increasing [ 28 , 30 , 32 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study conducted on individuals with chronic diseases in Taiwan, participants with an educational status of university or above had better health than those with a secondary or lower educational status. The study also observed that individuals with a higher educational status had a better health status than their peers 10 . In addition, Softa et al, 36 Polat and Kahraman 37 and Kulakçı et al 38 claimed that the difference between education level and the total score of healthy lifestyle behaviours was statistically significant.…”
Section: Discussionmentioning
confidence: 61%
“…To protect and improve the health of individuals with chronic diseases, several health behaviours must be changed at the same time 10 . Michishita et al followed middle-aged and elderly men for five years, and they found that some participants' healthy lifestyle behaviours, especially those who exercised lightly and did not snack before going to sleep, reduced their risk of chronic kidney disease 11 .…”
Section: Introductionmentioning
confidence: 99%
“…A pesar de ello, el sistema de salud peruano ha descuidado la salud de las personas de la tercera edad, no garantiza un envejecimiento saludable, y las intervenciones que se realizan no logran cubrir las demandas y necesidades de esta población, el modelo de atención actual no contribuye eficazmente al trabajo preventivo-promocional, pues las intervenciones son mayormente recuperativas con resultados parcialmente óptimos, por la logística precaria en el primer nivel de atención 12 ; por tanto, ante estas circunstancias el rol de los profesionales de la salud adquiere una importancia notable, para brindar las pautas y el acompañamiento progresivo en el manejo global de las patologías y sus complicaciones 2 . Así mismo, es necesario que las políticas sean integrales y se focalicen según las características de cada contexto sociodemográfico en el que residen los adultos mayores 13 , para abarcar a los menos favorecidos por su condición económica precaria 14 .…”
Section: Introductionunclassified